Interplay between sexual excitation and inhibition: impact on sexual function and neural correlates of erotic stimulus processing in women - Schmidt, Norina M.; Hennig, Juergen; Munk, Aisha J. L. (Frontiers in Behavioral Neuroscience, 2024)
Background: As outlined by the dual control model (DCM), individual differences in the regulation of sexual arousal following sexual stimulation depend on two distinct neurophysiological processes: sexual excitation (SE) and sexual inhibition (SI). Although associations with sexual function, behavior, and cue processing have been demonstrated in previous research, underlying neural correlates remain insufficiently explored. Moreover, interactive effects of SE/SI as proposed by the DCM, as well as factors impacting SE/SI properties, such as the use of oral contraceptives (OCs), have not received adequate attention in existing research.Methods: 90 healthy, sexually active women (n = 51 using OCs, n = 39 naturally cycling) completed an Emotional-Picture-Stroop-Paradigm (EPSP) while a 64-channel EEG was recorded. LPP amplitudes towards erotic and neutral stimuli were consecutively computed as a marker of motivational salience and approach motivation. Additionally, women provided self-reports of SE/SI and sexual function (SF). Moderation analyses were performed to assess interactive effects of SE/SI in predicting LPP amplitudes and SF.Results: Sexual function was negatively associated with SI levels but unrelated to SE. Higher SI was associated with reduced LPP amplitudes in response to erotic stimuli. This negative association was, however, attenuated for women high in SE, suggesting interactive effects of SE/SI. Furthermore, women using OCs reported lower SE compared to naturally cycling women.The observed findings provide additional psychophysiological evidence supporting the DCM and underscore the relevance of interactive SE/SI effects in stimulus processing and approach motivation. They also highlight the possible impact of OCs on psychosexual variables that warrants further research.